The role of the “Records card of immovable propertis” in the protection and conservation of architectural heritage 2nd half of the 20th century - Włodarczyk, Małgorzata (Protection of Cultural Heritage, 2016)
„Record cards of immovable properties” may be used for holding information about specific assets. This tool is of utmost importance for protecting and preserving architectural heritage assets built after the second World War in the second half of the 20th century. It allows for recognising a property in advance, defining the scope of protection (whether the entire property should be protected or only its particular elements), and specifying types of works which can be carried out to the property in question. This tool turns out to be particularly important in the event of changing ownership, carrying out renovation works or any other works pertaining to redevelopment, development, adaptation, etc. Additionally, it may be used for developing historic preservation guidelines for architectural designs and the areas they affect and, at the same time, preserving their initial form. Moreover, the tool in question allows historic preservation services to carry out such works to historic monuments and sites that will not only respect their cultural values but also „give them a new lease of life.” Furthermore, it may be used not only in scientific or academic works but also in works aimed at general public. In the current body of law, there are two types of „record cards of immovable properties.” The first one contains information on assets listed in the national register of historic monuments and sites. The second one provides data on assets not listed in this register - in this case, specific merit-related and graphical information is required. Its broader use by historic preservation service may result in increased effectiveness in preserving architectural heritage of the second half of the 20th century.